Formulation and Evaluation of Polyherbal Cream Containing Cinnamomum zeylanicum Blume, Glycyrrhiza glabra L and Azadirachta indica A. Juss. Extracts to Topical Use - Gyawali, Rajendra; Gupta, Rupesh Kumar; Shrestha, Sahana; Joshi, Rajendra; Paudel, Prem Narayan (Journal of Institute of Science and Technology, 2020)
Alcoholic extracts of medicinal plants Cinnamomum zeylanicum Blume, Glycyrrhiza glabra L, and Azadirachta indica A. Juss were subjected to the evaluation of antioxidant properties and combined for the cream formulation. The antioxidant property was determined by using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay and inhibition of lipid peroxidase assays. The cream formulation was designed using Minitab software and a central composite design was used to study the effect of dependent variables, steric acid and cetyl alcohol on the response variables such as, viscosity, pH, and spreadability. The phytochemical screening of extracts showed the presence of tannin, phenol, flavonoids, saponins, and alkaloids. Antioxidant properties of the extracts and their relative composition were found variable. Composition F3 (C. zeylanicum Blume: G. glabra L: A. indica A. Juss; 01: 02: 01) possessed the highest antioxidant capacity compared to other ratios. The cream prepared from this composition was found stable for pH, viscosity as well as antioxidant activity under normal condition (25) and accelerated condition (40 ). The cream with DPPH scavenging activity of 93.86 % at 15 µg/mL (IC50 8.58±0.30) and lipid peroxidase assay 90.93 % at 200 µg/mL (IC50 72.30±0.60) with pH 5.50 was found with a non-Newtonian positive thixotropic flow property. Parameters like pH, viscosity, and spreadability of the cream were within the acceptance range, and found stable and permeable